2005
DOI: 10.1081/jas-200044746
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Asthma and Asthma-Like Symptoms in Inner-City Schoolchildren

Abstract: This study investigates the prevalence of asthma and asthma-related symptoms in New Orleans inner-city schoolchildren. A cross-sectional survey of 1535 elementary, middle, and high school children (aged 5-18) was conducted by using the International Study of Asthma and Allergies in Childhood (ISAAC) written questionnaire. Lifetime prevalence of wheezing was 39.4%, and lifetime prevalence of asthma was 24.4%. Wheezing during the previous 12 months was reported by 25.7% of the sample. Twenty-one percent of respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
1
21
2
2
Order By: Relevance
“…ISAAC studies have shown that asthma prevalence is much higher in industrialized and western countries as compared to developing countries such as Asia and Africa [5]. In 2003 the ISAAC study in the urban city of Pune reported the prevalence of wheeze in the last 12 months to be 2.9% in school children aged 6-7 and 13-14 [6].…”
Section: Introductionmentioning
confidence: 99%
“…ISAAC studies have shown that asthma prevalence is much higher in industrialized and western countries as compared to developing countries such as Asia and Africa [5]. In 2003 the ISAAC study in the urban city of Pune reported the prevalence of wheeze in the last 12 months to be 2.9% in school children aged 6-7 and 13-14 [6].…”
Section: Introductionmentioning
confidence: 99%
“…18 This strategy for ascertainment of a lifetime diagnosis has been used by the Centers for Disease Control and Prevention to assess prevalence of asthma and in multiple clinical research studies. [19][20][21] …”
Section: Clinical Definitions and Data Collectionmentioning
confidence: 99%
“…The semitropical climate, with high humidity and lack of winter frost, may increase the risk of multiple allergen exposure. 8,12 To fill the data gap on exposure to home dust allergens in asthmatic children living in the Gulf South, we measured level of dust mite (Der p 1, Der f 1), cockroach (Bla g 1), dog (Can f 1), and cat (Fel d 1) allergen in homes of children with asthma living in inner-city New Orleans.…”
Section: Introductionmentioning
confidence: 99%